Numerical Simulation and Experimental Research of Oil-free Scroll Air Compressor Based on CFD - Jian, Sun; Bin, Peng; Bingguo, Zhu (Recent Patents on Mechanical Engineering, 2022)
Background: Compared with other types of compressors, although the scroll compressor has a simple structure and low noise, due to the limitation of the structure, it has defects such as excessively high discharge temperature, and has extremely high requirements on the machining accuracy of parts. The oil-free scroll compressor is a new type of scroll machine, which does not contain oil during the working process; it can be applied to cases with low displacement requirements and a high-pressure ratio. Objective: Taking a scroll compressor with a rated displacement of 0.6 m3/min as the research object, the analysis and research of the working performance parameters of the scroll compressor in actual work provide a certain theoretical basis for the improvement and optimization of the test prototype. Methods: The thermodynamic model of the scroll compressor in the actual working process is established by the variable-mass system thermodynamics and the control volume method. Based on the CFD method, a three-dimensional unsteady-state numerical simulation of the flow characteristics of the working fluid in the scroll compressor's working chamber is carried out in order to verify the thermodynamic model. Considering the accuracy of numerical simulation, a test platform with air as the working fluid is set up. Results: Through the thermodynamic model and numerical simulation, the changes of temperature, pressure and velocity in the working chamber of the scroll compressor with the orbiting angle of the main shaft as well as the gas force and torque acting on the orbiting scroll tooth are obtained. Through experiments, the law of volume flow and shaft power of the scroll compressor with the speed of change, and the law of the change of discharge temperature with pressure at different speeds are obtained. Conclusion: At the same time, the thermodynamic model established by considering heat transfer and leakage is more in line with the actual working process of the compressor; the mass exchange between adjacent working chambers of the scroll compressor has a greater impact on the temperature and pressure in the working chamber. Due to internal leakage and irreversible loss, such as heat transmission, there is a deviation between the theoretical volume flow and the actual volume flow.
Keywords: single scroll